Look, listen, learn, lead : a district-wide systems approach to teaching and learning in preK-12 - Smith, Jeffery (Jeffery O.); Caggianno, John; Maxlow, Kate Wolfe; Sanzo, Karen (Charlotte, NC : Information Age Publishing, Inc., 2021)
"Look, Listen, Learn, LEAD: A District-Wide Systems Approach to Teaching and Learning in PreK-12 lays out the transformational journey of Hampton City Schools (HCS), an urban school division of 30 schools in southeastern Virginia. Our school district faces numerous challenges, such as 62% of students receiving free and reduced-price lunch and 14% of students holding an IEP, and in 2015-2016, Hampton City Schools' state accreditation rate was approximately half the statewide rate and on a downward trend. In only three years, that was turned around and HCS exceeded the statewide accreditation rate, a more than 100% improvement with 100% of our schools accredited without conditions. We attribute this in large part to our dedicated educators and their implementation of district-wide systems for curriculum, instruction, checking for student understanding, climate, and culture. The goal of this book is to break down the process of what it takes to bring about large-scale educational change that is sustainable. We describe a process for developing a strong mission and vision to undergird the work around a variety of district-wide systems. This book provides insights into how to improve climate and culture, create a guaranteed and viable written curriculum, establish a process for evaluating its implementation, and create a balanced assessment framework to measure student success. Complete with example templates, action plans, and lessons learned, this book is a true example of theory-into-practice to bring about sustained improvement for all learners"--
Cover -- Series page -- Look, Listen, Learn, LEAD -- Library of Congress Cataloging-in-Publication Data -- Contents -- Preface -- Chapter 1: Leading for Systematic and Sustainable Change -- Chapter 2: Climate and Culture Leadership -- Chapter 3: Written Curriculum Leadership -- Chapter 4: Taught Curriculum Leadership -- Chapter 5: Assessed Curriculum Leadership -- Chapter 6: From Accountability to Responsibility -- About the Authors
Includes bibliographical references.
Print version record and CIP data provided by publisher; resource not viewed.
eBooks on EBSCOhost
Keywords: School improvement programs -- Virginia -- Hampton; Educational change -- Virginia -- Hampton; Educational leadership -- Virginia -- Hampton; School management and organization -- Virginia -- Hampton; Educational change; Educational leadership; School improvement programs; School management and organization; Virginia -- Hampton